2018
DOI: 10.1055/a-0603-7899
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Liver Enzymes and Insulin Resistance in Type 2 Diabetes Patients with Nonalcoholic Fatty Liver Disease

Abstract: Non-: alcoholic fatty liver disease (NAFLD) is prevalent worldwide, especially in patients with type 2 diabetes. Liver enzymes are the main warning signs of liver injury and insulin resistance (IR) is critical to NAFLD. This study was aimed to investigate the association between liver enzymes and insulin resistance in type 2 diabetes patients with NAFLD. Data from 212 diabetes patients with NAFLD were analyzed, including 118 males and 94 females who received care from 2014 to 2015. The patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…However, not all the studies supported the above conclusion. Sheng et al reported that some NAFLD patients possessed the normal ALT value, and the residual NAFLD patients had the elevated level of ALT [13]. Amarapurkar et al reported that the histological and clinical manifestation of NAFLD and NASH patients with normal ALT value were not different with the NAFLD and NASH patients with elevated ALT value [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not all the studies supported the above conclusion. Sheng et al reported that some NAFLD patients possessed the normal ALT value, and the residual NAFLD patients had the elevated level of ALT [13]. Amarapurkar et al reported that the histological and clinical manifestation of NAFLD and NASH patients with normal ALT value were not different with the NAFLD and NASH patients with elevated ALT value [22].…”
Section: Discussionmentioning
confidence: 99%
“…After removed the duplication, reviews, animal studies, and irrelevant resources, 34 potential studies were selected to further evaluation. After excluded 23 improper studies, a total of 11 studies with 4084 patients [13][14][15][21][22][23][24][25][26][27][28] which matched the inclusion criteria were included in this meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of NAFLD can be introduced by a model, which is a two-hit theory, in which it is stated that the disease is caused by the first-hit due to insulin resistance, obesity and dyslipidemia, and due to the second-hits, such as oxidative stress, pro-inflammatory cytokines and intestinal bacterial toxins, ultimately inflammation and fibrosis of liver cells are occurred (37). On the other hand, liver enzymes, like ALT, as an indicator of oxidative stress and inflammation are factors resulting in insulin resistance (38).…”
Section: Discussionmentioning
confidence: 99%
“…The extract of Erythrina abyssinica had significant effects on the serum alanine amino-transferase levels (ALT) which are a recognized marker of hepatocellular injury. Indeed, several epidemiologic association studies have shown that this enzyme is elevated in, and consequently can be used as a biomarker of NAFLD [52][53][54].…”
Section: Discussionmentioning
confidence: 99%